2009
DOI: 10.1007/s10714-009-0918-3
|View full text |Cite
|
Sign up to set email alerts
|

Pixel lensing

Abstract: Pixel lensing is gravitational microlensing of unresolved stars. The main target explored up to now has been the nearby galaxy of Andromeda, M31. The scientific issues of interest are the search for dark matter in form of compact halo objects, the study of the characteristics of the luminous lens and source populations and the possibility of detecting extra-solar (and extra-galactic) planets. In the present work we intend to give an updated overview of the observational status in this field.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…There have also been searches for 'pixel-lensing' in M31 where unresolved stars are being microlensed causing a pixel to brighten. About 30 possible microlensing events have been detected [97], but there is still some debate as to the extent to which self-lensing distorts the statistics [98]. There does however seem to be a good case for around 25% of the M31 halo to be in the form of compact bodies [99,100].…”
Section: Appendix A: Microlensing Constraints and Solar Mass Pbhsmentioning
confidence: 99%
“…There have also been searches for 'pixel-lensing' in M31 where unresolved stars are being microlensed causing a pixel to brighten. About 30 possible microlensing events have been detected [97], but there is still some debate as to the extent to which self-lensing distorts the statistics [98]. There does however seem to be a good case for around 25% of the M31 halo to be in the form of compact bodies [99,100].…”
Section: Appendix A: Microlensing Constraints and Solar Mass Pbhsmentioning
confidence: 99%
“…Observations and studies of the pixel‐lensing microlensing events towards M31 are still not conclusive with respect to the amount of SL and MACHO lenses (see Calchi Novati 2010b, for recent review). However, the most recent analysis of the data tends to be inclined towards SL as being the only explanation of the observed signal (Calchi Novati 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Ibata et al (1999) and Méndez & Minniti (2000) used the Hubble Deep Field North (Williams et al 1996) and South (Casertano et al 2000) data to constrain the stellar content of the Galaxy. They proposed that the faint blue objects observed in these fields are old halo white dwarfs that would be consistent with the observed microlensing events toward the Large Magellanic Cloud (Alcock et al 2000;Calchi Novati 2010) and would explain part of the dark matter in the solar neighborhood. Kilic et al (2004Kilic et al ( , 2005, Pirzkal et al (2005), and Mahmud & Anderson (2008) showed that some of these faint blue objects are confused with quasars and an extensive study including proper motion measurements and spectral energy distribution (SED) fitting is required to identify stars in deep HST images.…”
Section: Introductionmentioning
confidence: 59%